PENGARUH PRESTASI KERJA TERHADAP KUALITAS KERJA DI DINAS PERIKANAN KABUPATEN WAJO - Qadar, Jamal; Rusyadi, Aulia Anugrah; Syamsiar, Syamsiar (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2025)
This study aims to analyze work performance, analyze work quality, and analyze the influence of work performance on work quality at the Wajo Regency Fisheries Service. The research method used was a survey research with a quantitative associative approach. Data collection techniques used observation, documentation, and questionnaires. The research population was 70 people with a sample of 41 people using the Slovin technique. Data analysis techniques used descriptive statistics and quantitative associative data analysis with SPSS version 28.0. The results showed that work performance at the Wajo Regency Fisheries Service was in the very good category with a score of 3,718, and work quality was also in the very good category with a score of 3,378. Correlation analysis showed a correlation value of 0.642 which indicates a positive and strong relationship between work performance and work quality. Regression analysis results showed an R Square value of 0.412, meaning that 41.2% of work quality variation can be explained by work performance. The significance test showed a sig value of 0.000 < 0.05, so it can be concluded that work performance has a positive and significant effect on work quality at the Wajo Regency Fisheries Service.